Positive regulation of p53 stability and activity by the deubiquitinating enzyme Otubain 1 - Sun, Xiao-Xin (Nature Publishing Group, 2012)
The ubiquitin (Ub)–proteasome system plays a pivotal role in the regulation of p53 protein stability and activity. p53 is ubiquitinated and destabilized by MDM2 and several other Ub E3s, whereas it is deubiquitinated and stabilized by Ub-specific protease (USP)7 and USP10. Here we show that the ovarian tumour domain-containing Ub aldehyde-binding protein 1 (Otub1) is a novel p53 regulator. Otub1 directly suppresses MDM2-mediated p53 ubiquitination in cells and in vitro. Overexpression of Otub1 drastically stabilizes and activates p53, leading to apoptosis and marked inhibition of cell proliferation in a p53-dependent manner. These effects are independent of its catalytic activity but require residue Asp88. Mutation of Asp88 to Ala (Otub1(D88A)) abolishes activity of Otub1 to suppress p53 ubiquitination. Further, wild-type Otub1 and its catalytic mutant (Otub1(C91S)), but not Otub1(D88A), bind to the MDM2 cognate E2, UbcH5, and suppress its Ub-conjugating activity in vitro. Overexpression of Otub1(D88A) or ablation of endogenous Otub1 by siRNA markedly impaired p53 stabilization and activation in response to DNA damage. Together, these results reveal a novel function for Otub1 in regulating p53 stability and activity.